(3TQM CHjGJ JaSjQ GdcTGa ddReNTQis - (3TeS GdOjf eMeO Hf SdjeGf Hf eMeO GdNWjHs; (3GdReNTQj , LGQ Gddg CHh GdbGSe eMehO Hf YeQ Hf eMeO GdNhGQRej GdReNTQj, GdReNTQj,J (B538 (3g` s
(3ChdgG (B:s
(3hHYO aEf CNkG ef ENhGfi hNdU NdG ai ETGQI Edi HYO Cf TQMJ CHjGJ cJGH GdeaUd Cf CTQM CHjGJ GdcTGa ai GdJaSjQ GdPi Ufag GdEeGe GdYdGeI LGQ Gddg GdReNTQi ShQI GdaGJMI efgG bhd GdTGYQ s
(3BNQgG (B:s
(3EYde Cf GdefGaSI hGdZHWI ai GdNjQGJ hGdecQeGJ MSfI bGd Gddg JYGdi (B( (3hai Pdc adjJfGaS GdeJfGaShf (B) (3gPG BNQ TQM CHjGJ GdcTGa hGdMeO ddg Mb MeOg hUdi Gddg Ydi NjQ Ndbg eMeO hBdg GdWjHjf GdWGgQjf hCUMGHg CLeYjf hSde cKjQkG QH ENJe HGdNjQ HaVds
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HChdgG agQS ddeNWhWs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs